Is High-Intensity Interval Training More Effective on Improving Cardiometabolic Risk and Aerobic Capacity Than Other Forms of Exercise in Overweight and Obese Youth? a Meta-Analysis - Herrera-Valenzuela, T; Garcia-Hermoso, A (Blackwell Publishing Ltd, 2016)
Summary: Background: The scientific interest in high-intensity interval training (HIIT) has greatly increased during recent years. Objective: The objective of this meta-analysis was to determine the effectiveness of HIIT interventions on cardio-metabolic risk factors and aerobic capacity in overweight and obese youth, in comparison with other forms of exercise. Data sources: A computerized search was made using seven databases. Study eligibility criteria: The analysis was restricted to studies that examined the effect of HIIT interventions on cardio-metabolic and/or aerobic capacity in pediatric obesity (6-17years old). Participants and interventions: Nine studies using HIIT interventions were selected (n=274). Study appraisal and synthesis methods: Standarized mean difference (SMD) and 95% confidence intervals were calculated. The DerSimonian-Laird approach was used. Results: HIIT interventions (4-12week duration) produced larger decreases in systolic blood pressure (SMD=0.39; -3.63mmHg) and greater increases in maximum oxygen uptake (SMD=0.59; 1.92ml/kg/min) than other forms of exercise. Also, type of comparison exercise group and duration of study were moderators. Conclusions: HIIT could be considered a more effective and time-efficient intervention for improving blood pressure and aerobic capacity levels in obese youth in comparison to other types of exercise. © 2016 World Obesity.